Revitalisasi Desa Wisata Bumi Perkemahan Ngijo dalam Mengoptimalkan Potensi Wisata di Kelurahan Srimulyo, Piyungan, Bantul, Yogyakarta - Rosiana Puspitasari, Dyah; Maulia, Jeni; Lestiani, Lia; Sandy Skani, Albertus; bowo, Herpra; Kumara, Pienta; Heggar Arbitya Susanto, Muhammad; Muhammad Dafa Febriansyah; Bernandus Aristono Kawen; Said Azhar Zulviqri; Zainal Aspiah; Aditya Anang Fauzi; Argo Triyo Prakoso; Muhammad Afief Miftah (Swadaya: Jurnal Pengabdian Masyarakat, 2023)
The aim of this community service is to revitalize Bumi Perkemahan Ngijo by encouraging community participation in this positive endeavor. The method employed in this research is the Participatory Observation Method, where researchers actively engage with the community in the revitalization activities at Bumi Perkemahan Ngijo. In essence, to achieve the objectives of this community service, the service team utilizes a participatory approach. The outcomes of these activities reveal that Bumi Perkemahan Ngijo, which has ceased operations since the COVID-19 pandemic, has resulted in damage to several facilities, rendering them unusable. Students from Janabadra University's Community Service Program have endeavored to repair facilities, engage in reforestation, install signboards, and provide waste disposal facilities.